In Vitro and In Vivo Wound Healing Activity of Astragalus floccosus Boiss. (Fabaceae). (29th March 2022) - Akbari, Fatemeh; Azadbakht, Mohammad; Bagheri, Ali; Vahedi, Lale
Abstract : Estrogens are a group of sex hormones which have receptors on the skin and lead to increased cells and wound healing. Normally isoflavonoids are present in Astragalus floccosus Boiss. (Leguminosae). Therefore, the present study was conducted to evaluate the presence of isoflavonoids in A. floccosus' rich fraction of flavonoid and evaluate its wound healing effect accordingly. Flavonoids were evaluated by LCMS. Scratch was conducted and the medium culture was treated with the Astragalus' rich fraction of flavonoid (RFF) and was compared with nontreated culture during 48 hours. In addition, in vivo full-thickness wound healing evaluation was performed on rats. The rats were put into four groups and treated on a daily basis for 21 days with a cream containing 1.5% of the RFF (group 1), silver sulfadiazine (group 2), and Vaseline (group 3) separately. The nontreated group (group 4) was created for a better comparison. During the examination, wound size was evaluated and histopathological examination was performed. Herbal analysis detected 11 flavonoids, including 2 isoflavonoids, Calycosin-7-O-beta-D-glucoside and Formononetin, in the RFF. In vitro scratch wound healing showed significant improvement with RFF treatment in comparison to nontreated medium. Furthermore, in vitro drug release of Astragalus ointment showed a stationary line during 24 h and 0.14 mg/ml of flavonoid penetrated the skin. In vivo wound size evaluation showed significant improvement in the group treated with the RFF in comparison to other groups. Histopathological results indicated that congestion, edema, inflammation, necrosis, and angiogenesis decreased during the examination and fibroblast proliferation fibrosis epithelization was increased especially in the RFF group in comparison to the silver sulfadiazine and free groups. In conclusion, A. floccosus showed that wound healing activity in both in vitro and in vivo analyses can be attributed to the presence of isoflavonoids with estrogen-like activity in this plant.